Application of laryngeal mask airway anesthesia with preserved spontaneous breathing in children undergoing video-assisted thoracic surgery - Huang, Jinjin; Huang, Wenfang; Zhang, Jie; Tan, Zheng; Wang, Dongpi (Frontiers in Pediatrics, 2023)
Purpose: To investigate the feasibility and safety of non-intubated general anesthesia with spontaneous breathing combined with paravertebral nerve blocks (PVNB) in young children undergoing video-assisted thoracic surgery (VATS) and to determine its significance for rapid recovery after pediatric thoracic surgery. Methods: The data of 46 children aged 6 months to 36 months with an American Society of Anesthesiologists (ASA) status of I-II who underwent elective VATS under general anesthesia were retrospectively analyzed. Of these patients, 25 underwent non-intubated general anesthesia with spontaneous breathing combined with PVNB (non-intubation group), and 21 received conventional intubated general anesthesia combined with local infiltration anesthesia (intubation group). The following perioperative parameters were compared between the two groups: heart rate (HR), mean arterial pressure (MAP), saturation of pulse oximetry (SpO2), partial pressure end-tidal carbon dioxide (PETCO2), time from the completion of the operation to extubation or removing laryngeal masks, time to first feeding after the operation, length of postoperative in-hospital stay, incidence of postoperative complications, and hospitalization expenses. Results: The operations were completed successfully in both groups. When the non-intubation group was compared with the intubation group, the minimal SpO2 level during the surgery was higher (93% vs. 88%, P<0.001), might indicate better oxygenation; the duration of surgery and intraoperative blood loss were not significantly different; and the duration of anesthesia (P = 0.027), time from the completion of the operation to extubation (P<0.001), time to the first feeding after surgery (P<0.001), length of postoperative in-hospital stay (P<0.001), and hospitalization expenses (P<0.001) were significantly reduced. The incidence of postoperative complications was not significant different. Conclusions: Non-intubated general anesthesia with spontaneous breathing combined with PVNB is safe and feasible in young children undergoing VATS and can promote rapid recovery in young children undergoing thoracoscope surgery.